HUBUNGAN KARAKTERISTIK NASABAH DENGAN ATRIBUT PRODUK TABUNGAN PADA BPR SYARIAH BANGUN DRAJAT WARGA YOGYAKARTA - Astuti (2011)
This study was conducted to examine the characteristics of customer relationships with savings on product attributes on BPR Syariah Bangun Drajat Warga Yogyakarta by using a correlation test analysis. This study uses the variable characteristics of the customer (sex, profession and education) with variable product attributes (profession, product quality, education and product quality, sex and product design, profession and product design, education and product design, sex and brand, pr